Rancang Bangun Bilah Turbin Angin Sumbu Horizontal Tipe Taper Dengan Menggunakan Airfoil Naca 6512 di PT. Lentera Bumi Nusantara - Fahrul Rofi; Viktor Naubnome; Arifin Arifin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Utilization of alternative energy such as wind energy is one solution to be able to produce electrical energy through this wind turbine. The potential for wind energy in Indonesia has an average of 2-7 m/s which can be utilized for renewable energy. The purpose of this taper blade design is to find out the best performance so that the taper blade design with Airfoil NACA 6512 can operate on wind turbines designed for wind speeds in Indonesia. This NACA 6512 airfoil has a high Cl/Cd value for use on taper blades. This design uses the BEM (Blade Element Momentum) method as a simulation performance analysis by entering the results of the blade geometry. Using Solidworks Software to create 3D blade designs. The dimensions of the NACA 6512 taper blade have a radius of 0.8 m, a chord width of 12 cm at the base and 6 cm at the tip of the blade. Has a maximum Cp value of 53% at TSR 6. At a maximum rpm of 788 Rpm has a maximum power of 1149 W. The results of field testing have a maximum charging power of 279.11 W on the first day of testing and the largest average charging is 36.75 W. the power that can be obtained by this taper blade is 439.99 Wh.